Sex Difference in Mortality for Premature and Low Birth Weight Neonates: A Systematic Review - Vu, Huy Duc; Dickinson, Corrine; Kandasamy, Yogavijayan (American Journal of Perinatology, 2018)
Objective Advances in neonatology have made possible the survival of neonates with lower gestational ages and birth weights. Nevertheless, findings remain of a sex difference in mortality for premature and low birth weight (LBW) neonates with male sex often associated with poorer outcome (the “male disadvantage”). Through literature review, this article will seek clarification of the existing evidence regarding the association between sex and mortality at discharge from neonatal intensive care units (NICUs) for premature and LBW neonates.Methods A systematic review was conducted in Medline and Google Scholar with subsequent search of study reference lists.Results The database search yielded 349 articles and an additional 11 were identified from study reference lists. A final 32 studies were reviewed. Of these, 26 studies demonstrated worse male mortality outcome and 6 studies reported no sex difference in mortality.Conclusion The majority of reviewed studies found poorer male mortality outcome. A small number of studies maintained a null association between sex and mortality. This indicates male premature and LBW neonates experience higher risk of mortality by discharge compared with females, an observation which may inform clinical decision making in the NICU.
Keywords: mortality; survival; sex difference; neonate; premature; low birth weight